Animal welfare in Costa Rican specialized dairy herds from a dairy cooperative - DiGiacinto Villalobos, Alice (2015)
The objective of this study was to characterize animal welfare in specialized dairy herds in Costa Rica from a dairy cooperative with national distribution. This instrument directly measured welfare of animals in each farm in terms of housing, nutrition, health and behavior, which allows to classify farms into a category among excellent, good, acceptable and non-classified, based on a 0 to 100 score. Sixty farms were evaluated with this protocol in different parts of the country. Fifty-five percent of farms were classified as good, while 37.0% as acceptable. Items with higher scores correspond to housing (82.8%) and behavior (55.7%). On the other hand, the lowest values were health (40.1%) and nutrition (38.1%). The main problem was water supply, both in quantity and quality. It was found that stall or semi-stall production systems provide animals with better food and water conditions than those in continuous grazing systems; however, continuous grazing systems offer better benefits in terms of comfort and housing. If the deficient aspects are improved in both systems, it is possible to offer good animal welfare conditions in any cattle production system.